PENGARUH UU ITE TERHADAP KEBEBASAN BEREKSPRESI DI MEDIA SOSIAL: The Impact of the ITE Law on Freedom of Expression on Social Media - Mihfatul Ihzan (Yayasan Al-Amin Qalbu, 2025)
In today's digital era, people have the convenience of expressing opinions, sharing experiences, or stating opinions through social media. However, this freedom of expression is also often accompanied by violations related to the Electronic Information and Transactions Law (UU ITE), which makes many people afraid to express themselves on social media due to a lack of understanding of the law. The ITE Law is viewed positively by some people, but there are also those who see it from a negative side. This study uses a normative legal research method with a literature approach, collecting legal materials through literature studies that refer to primary and secondary legal materials, and using a statutory approach. The purpose of this study is to provide information about things to consider when using social media, understand the influence of news on social media on self-expression, and provide guidance for using social media wisely. With a correct understanding of the ITE Law, it is hoped that people will not feel worried about expressing themselves freely on social media, and can become responsible users